ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SETELAH MERGER PADA PT GUNAWAN DIANJAYA STEEL TBK (GDST) - Fathan Azhar Salafi; Sri Murwanti (Departemen Manajemen, 2023)
This study addresses the issue of comparing the financial performance of PT Gunawan Dianjaya Steel Tbk before and after the merger. This study uses secondary data from PT Gunawan Dianjaya Steel Tbk's quarterly financial reports from the four years prior to the merger and the four years following the merger as part of a descriptive comparison study with a quantitative methodology. Data sources include PT Gunawan Dianjaya Steel Tbk's website and the Indonesian Stock Exchange's website (IDX). The analysis of this study made use of the paired sample t test and the Shapiro-Wilk normality test. The findings revealed that the debt-to-equity ratio (DER), current ratio (CR), and total asset turnover ratio (TATO). While there is no discernible variation between the ratios of return on assets (ROA) and net profit margin (NPM) at PT Gunawan Dianjaya Steel Tbk before and after the merger.